Kim Gordon - no icon - Gordon, Kim 1953- (Rizzoli, 2020)
As cofounder of legendary rock band Sonic Youth, best-selling author, and celebrated artist, Kim Gordon is one of the most singular and influential figures of the modern era. This personally curated scrapbook is an edgy and evocative portrait of Gordon s life, art, and style. Spanning from her childhood on Californian surf beaches in the 60s and 70s to New York s downtown art and music scene in the 80s and 90s where Sonic Youth was born. Through unpublished personal photographs, magazine and newspaper clippings, fashion editorials, and advertising campaigns, interspersed with Gordon s song lyrics, writings, artworks, private objects, and ephemera, this book demonstrates how Kim Gordon has been a role model for generations of women and men
Keywords: Gordon, Kim -- 1953-; Geschichte 1960-2000; Fotografie; Kunst; Einklebebuch; Gordon, Kim / 1953- / Pictorial works; Gordon, Kim / 1953-; Photobooks; Pictorial works; Bildband